Muslim Religious Behavior in Facing Pandemic - Abdul Fatah (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This paper analyzes comprehensively how the pattern of Muslim religious behavior in dealing with pandemics such as smallpox, cholera, SARS, Ebola, Covid-19, monkeypox and so on. The method used is thematic maudhu'i by collecting the words bala' and tha'un in the hadith. The results of this study produce the concept of religious behavior for Muslims based on the hadith of the prophet Muhammad SAW to deal with the pandemic. The results of the study are as follows: In facing trials in the form of pandemic such as Covid-19 that still persists in the soceity is by patient, namely patient in action in the form of vaccines and application of health protocols then patient in attitude that is surrender and sincerity towards trials and leave everything to Allah SWT. (al-Baqarah/2:155) The Prophet gave good news to those who are patient in facing the pandemic, if they die, they will be rewarded with martyrdom (Sahih Bukhri: 2.618). Muslims must maintain a clean and healthy environment to increase immunity so that they are not easily attacked or contracted by disease. (Sahih Bukhari:1.747) Regional quarantine or lockdown has been taught by the Prophet as an effort to stop the spread of the pandemic (Sahih Bukhari:3.214) after trying hard physically, then praying for protection from Allah SWT from all kinds of bad trials (Sahih Bukhari 5871), Sunan Abu Dawud: 1329).